Nociceptive transmission and modulation via P2X receptors in central pain syndrome. Issue 1 (December 2016) - Kuan, Yung-Hui; Shyu, Bai-Chuang
Abstract Painful sensations are some of the most frequent complaints of patients who are admitted to local medical clinics. Persistent pain varies according to its causes, often resulting from local tissue damage or inflammation. Central somatosensory pathway lesions that are not adequately relieved can consequently cause central pain syndrome or central neuropathic pain. Research on the molecular mechanisms that underlie this pathogenesis is important for treating such pain. To date, evidence suggests the involvement of ion channels, including adenosine triphosphate (ATP)-gated cation channel P2X receptors, in central nervous system pain transmission and persistent modulation upon and following the occurrence of neuropathic pain. Several P2X receptor subtypes, including P2X2, P2X3, P2X4, and P2X7, have been shown to play diverse roles in the pathogenesis of central pain including the mediation of fast transmission in the peripheral nervous system and modulation of neuronal activity in the central nervous system. This review article highlights the role of the P2X family of ATP receptors in the pathogenesis of central neuropathic pain and pain transmission. We discuss basic research that may be translated to clinical application, suggesting that P2X receptors may be treatment targets for central pain syndrome.